2015
DOI: 10.1111/cts.12357
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Informatics for Integrating Biology and the Bedside (i2b2) into Predoctoral Trainee Curriculum to Evaluate Student‐Generated Hypotheses

Abstract: As part of the Clinical and Translational Science Institute pre-doctoral TL1 training program at the Pennsylvania State University, a multidisciplinary team of pre-doctoral trainees representing the Chemistry, Neurosurgery, Nutritional Sciences, and Public Health Sciences departments were introduced to the NIH-sponsored Informatics for Integrating Biology and the Bedside (i2b2) database to test the following student-generated hypothesis: children with iron deficiency anemia (IDA) are at increased risk of atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thus, screening and treatment would be part of currently established procedures. Although the link between correcting IDA and improving hearing health is not established, it is known that both IDA and hearing loss have negative effects related to attention and scholastic performance, which are improved with treatment (Abbas & Valli, 2012;Bener, Kamal, Bener, & Bhugra, 2014;Cortese, Angriman, Lecendreux, & Konofal, 2012;Halterman, Kaczorowski, Aligne, Auinger, & Szilagyi, 2001;Konofal, Lecendreux, Arnulf, & Mouren, 2004;Lahat et al, 2011;Millichap, Yee, & Davidson, 2006;Schieffer, Peters, Richter, Loc, & Pawelczyk, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, screening and treatment would be part of currently established procedures. Although the link between correcting IDA and improving hearing health is not established, it is known that both IDA and hearing loss have negative effects related to attention and scholastic performance, which are improved with treatment (Abbas & Valli, 2012;Bener, Kamal, Bener, & Bhugra, 2014;Cortese, Angriman, Lecendreux, & Konofal, 2012;Halterman, Kaczorowski, Aligne, Auinger, & Szilagyi, 2001;Konofal, Lecendreux, Arnulf, & Mouren, 2004;Lahat et al, 2011;Millichap, Yee, & Davidson, 2006;Schieffer, Peters, Richter, Loc, & Pawelczyk, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, improvement and monitoring systems are the most basic function. Pittman et al [15] utilized i2b2 and N2QOD to study time and cost efficiency of i2b2 and Research Electronic Data Capture (REDCap) system. They recognized errors in human data entry, the time-consuming process, and difficulty extracting accurate coding from different types of note styles, but demonstrated cost effective effectiveness with i2b2 compared to without i2b2.…”
Section: Research Articlementioning
confidence: 99%
“…In fact, current preliminary data in this study was used for grant application subsequently awarded. Schieffer et al [15] suggested that i2b2 could be utilized to test a predocotoral trainee curriculum, and that student generated research hypotheses could be tested. When the investigators would like to review institutional preliminary data, the result is available within a reasonable time period.…”
Section: Research Articlementioning
confidence: 99%